Eating eggplants as a cucurbit feeder: Dietary shifts affect the gut microbiome of the melon fly Zeugodacus cucurbitae (Diptera, Tephritidae). Issue 4 (16th August 2022) - Hendrycks, Wouter; Delatte, Hélène; Moquet, Laura; Bourtzis, Kostas; Mullens, Nele; De Meyer, Marc; Backeljau, Thierry; Virgilio, Massimiliano
Abstract: While contemporary changes in feeding preferences have been documented in phytophagous insects, the mechanisms behind these processes remain to be fully clarified. In this context, the insect gut microbiome plays a central role in adaptation to novel host plants. The cucurbit frugivorous fruit fly Zeugodacus cucurbitae (Diptera, Tephritidae) has occasionally been reported on "unconventional" host plants from different families, including Solanaceae. In this study, we focus on wild parental (F0 ) adults and semiwild first filial (F1 ) larvae of Z. cucurbitae from multiple sites in La Réunion and explore how the gut microbiome composition changes when this fly is feeding on a noncucurbit host ( Solanum melongena ). Our analyses show nonobvious gut microbiome responses following the F0 –F1 host shift and the importance of not just diet but also local effects, which heavily affected the diversity and composition of microbiomes. We identified the main bacterial genera responsible for differences between treatments. These data further stress the importance of a careful approach when drawing general conclusions based on laboratory populations or inadequately replicated field samples. Abstract : We investigated how the gut microbiome composition changes in a cucurbit‐feeding fly Zeugodacus cucurbitae when it feeds on atypical solanaceous hosts instead of typical cucurbit hosts. Wild parental (F0 ) adults and semiwild first filial (F1 ) larvae of Z. cucurbitae collected from two locations in Réunion Island showed heterogeneous microbiome responses across host plants. This study shows how local processes and host plants can strongly affect the composition of the insect microbiome and the importance of using adequately sampled populations.